Pengaruh Metode Discovery Learning dan Persepsi Kinestetik Terhadap Hasil Pembelajaran Bola Voli - Dewi Apriliasari; Tedi Purbangkara; Febi Kurniawan (Universitas Singaperbangsa Karawang, 2022)
The purpose of this study was to determine whether there was an influence of the Discovery Learning Method and Kinesthetic Perception on the Results of Volleyball Learning. To answer the formulation of this research, the researcher used a quantitative approach with experimental methods. The research was conducted at SMAN 1 Cilamaya with the type of research purposive sampling the population was taken in class X with a population of 432 and took 2 classes as samples with a total of 72 students. The results of the research that has been carried out with independent-sample t-test, experimental class pre-test and control class pre-test can be seen the probability value (significance) with equal variance assumed (assumed both variants are the same) is 0.323 > 0.05 then Ho received. before being given the same treatment. post-test experimental class and post-test control class can be seen the probability value (significance) with equal variance assumed (assumed both variants are equal) is 0.189 > 0.05 then Ho is accepted. The results of this study indicate that the two variants are the same or there is no significant difference between the post-test of the experimental class and the post-test of the control class.